Constitutionalism and democratic transitions - Federico, Veronica; Fusaro, Carlo (Firenze University Press, 2006)
The book - as the outcome of a research performed by the University of Florence and the United States Institute of Peace of Washington - explores the role of law in the process of democratic transition in South Africa. More specifically it emphasize how constitutional law may contribute to "civilize" apparently unreconcilable conflicts, a part from laying down the foundations of the new legal order and institutions.
The book - as the outcome of a research performed by the University of Florence and the United States Institute of Peace of Washington - explores the role of law in the process of democratic transition in South Africa. More specifically it emphasize how constitutional law may contribute to "civilize" apparently unreconcilable conflicts, a part from laying down the foundations of the new legal order and institutions.
English
Keywords: Peace studies & conflict resolution; Constitutional & administrative law; diritto; democrazia; sud africa; democracy; south africa; human rights; Burundi; Constitutionalism